Development of Digital Teaching Modules for Pancasila Education Subjects Based on Local Wisdom of Malay Culture at SMAN 1 Lingga - Fathussalamiah; Encik Abdulhajar; Nevrita; Zaitun (Raja Zulkarnain Education Foundation, 2025)
This study aims to develop a digital teaching module for Pancasila Education subjects based on local wisdom of Malay culture for grade X students. The study was conducted at SMAN 1 Lingga, Lingga Regency, Riau Islands Province in the odd semester of the 2025/2026 academic year. The research subjects consisted of grade Pancasila Education subject teachers, grade X-3 students and material and media validator experts. The research method used Research and Development (R&D) with the ADDIE model including the stages of Analyze, Design, Develop, Implement, and Evaluate. Data collection instruments were in the form of expert validation sheets, teacher and student response questionnaires, and learning implementation observation sheets. Data analysis used a qualitative and quantitative descriptive approach with a percentage formula. The results of material expert validation reached 100% in the very feasible category, media expert validation 90% in the very feasible category. Teacher responses showed a score of 97% in the very practical category, observation of learning implementation 92% in the very good category, and student responses 95% in the very practical category. A digital teaching module based on local Malay cultural wisdom has proven valid, practical, and effective in enhancing understanding of Pancasila values through contextualization of local culture.